2017
DOI: 10.3389/fimmu.2017.01757
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 1 Plays an Acetylation-Independent Role in Influenza A Virus Replication

Abstract: Influenza A viruses (IAVs) take advantage of the host acetylation system for their own benefit. Whether the nucleoprotein (NP) of IAVs undergoes acetylation and the interaction between the NP and the class I histone deacetylases (HDACs) were largely unknown. Here, we showed that the NP protein of IAV interacted with HDAC1, which downregulated the acetylation level of NP. Using mass spectrometry, we identified lysine 103 as an acetylation site of the NP. Compared with wild-type protein, two K103 NP mutants, K10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…However, it seems that downregulation of both HDAC1 and HDAC3 by virus infection was not correlated with the decreased levels of histone H3 acetylation, which emphasized the complexity of the mechanisms for the regulation of histone acetylation following virus infection. It has been reported that HDAC1 regulates influenza A virus (IAV) replication independent of its deacetylation activity [ 41 ]. HDAC1 stimulates host type I interferon antiviral response, therefore IAV infection decreases HDAC1 expression for efficient replication [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that downregulation of both HDAC1 and HDAC3 by virus infection was not correlated with the decreased levels of histone H3 acetylation, which emphasized the complexity of the mechanisms for the regulation of histone acetylation following virus infection. It has been reported that HDAC1 regulates influenza A virus (IAV) replication independent of its deacetylation activity [ 41 ]. HDAC1 stimulates host type I interferon antiviral response, therefore IAV infection decreases HDAC1 expression for efficient replication [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…No HDAC1 contains 482 amino acids, identified in 1996 by Taunton et al (17). HDAC1 regulates genes involved in cell differentiation and the cell cycle, and participates in the development of various diseases such as viral infectious diseases, degenerative diseases and cancer (18)(19)(20). HDAC1 can mediate site-specific DNA-binding transcriptional repression and a high level of HDAC1 is observed in tumor invasion and metastasis (21).…”
Section: Expression Of Hdac3 Mrna Clinicopathological ---------------mentioning
confidence: 99%
“…the nuclear import of NP and suppressing the TBK1-IRF3 signal pathway (Chen et al, 2017) (Table 1 and Figure 2).…”
Section: Ptms Involved In Uncoating and Nuclear Import Of Iav Vrnps Amentioning
confidence: 98%
“…The NP-interacting protein TRIM14 stimulates K48-linked ubiquitination and proteasomal degradation of NP, leading to a reduced efficiency in NP transportation from the cytoplasm to the nucleus and a subsequent inhibition of viral replication ( Wu et al, 2019 ) ( Table 1 and Figure 2 ). Meanwhile, HDAC1 interacts with NP, resulting in a decreased level of NP acetylation, thus facilitating viral replication through promoting the nuclear import of NP and suppressing the TBK1-IRF3 signal pathway ( Chen et al, 2017 ) ( Table 1 and Figure 2 ).…”
Section: Ptms Involved In the Viral Entry Process Of Iavmentioning
confidence: 99%